Patient with Purulent Pericardial Effusion Revealing Squamous Cell Lung Carcinoma - Karim Badaoui; Mounia El Mourid; Hatim Aminezahidi; Haja Rbendahou; Fatima Zaha Talhi; Halima Anniche; Nacer Drighil; Rachida Habbal (International Journal of Cardiovascular Practice)
Bacterial pericarditis is a rapidly progressive infection sown with heavy mortality. It usually occurs as a secondary infection to either a contiguous or hematogenous spread from a distant focus of infection. The primary involvement of the pericardium without evidence of underlying infection disease elsewhere, is sporadic. We present a unique case of a 69 -year-old patient who was diagnosed as having purulent acute bacterial pericarditis caused by Streptococcus pneumonia, revealing an underlying squamous cell lung carcinoma in the cardiology department of IBN ROCHD University hospital of Casablanca.